Economic Implications and Communication Strategy for Investigators in Handling Criminal Acts of Illegal Sodium Cyanide Trafficking - Harimbawa, Gede (International Journal of Economics Development Research (IJEDR), 2024)
This research starts from the problem of implementing political strategies, which can provide support and aspirations that can be channeled or vice versa. In the context of the police, communication strategies are used to create and implement rules, especially in the investigation and investigation process by increasing the ability and opportunity for the community to express all forms of problems and channel information that they have hidden so that it is hoped that this can be realized or create reciprocal communication between superstructure and infrastructure in the disclosure of effective communication strategies. The aim of this research is to reveal, describe and analyze investigators' communication strategies in handling criminal acts of illegal sodium cyanide trafficking using a cultural approach. This research method is proposed by the author using a qualitative descriptive method which is to describe, explain and describe the objects studied by Arikunto, (2006). Descriptive qualitative research is in the form of research using a case study method or approach. The results of the research show that with this communication strategy, investigators can easily complete their investigative tasks because this effective communication strategy makes it easier for the investigation process or seeking information from the suspect because the suspect feels unlimited, without coercion, and honestly explains what he has done in this case. This is a criminal act committed within the jurisdiction of the West Nusa Tenggara Regional Police. The conclusion of this research is that steps to prevent investigators are of particular concern in line with the growing public awareness that the trade in cyanide as a deadly item is difficult for the public to avoid because it cannot be traded.